2019
DOI: 10.3390/app9071432
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of a Graphene Oxide Layer into a Cu/SiO2/Pt Structure to Overcome Performance Degradation in a Vaporless Environment

Abstract: A Cu/SiO 2 /Pt structure is usually used to study the resistive memory properties of an electrochemical resistive random access memory. It can be reversibly switched between low-and high-resistance states by using DC voltages in the atmosphere. However, its resistive switching behavior disappears in a vaporless environment because no conducting filaments can be formed within the Cu/SiO 2 /Pt structure. This study inserted a graphene oxide (GO) layer to fabricate a Cu/GO/SiO 2 /Pt structure that could be resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Liu et al [1] inserted a graphene oxide (GO) layer, manufactured as a Cu/GO/SiO 2 /Pt structure, which could be resistively switched in a vaporless environment. The X-ray photoelectron spectra depth profile of this structure showed that the GO film caused Cu ionization in a vaporless environment with migration of Cu ions in an electrical field to the Pt electrode.…”
mentioning
confidence: 99%
“…Liu et al [1] inserted a graphene oxide (GO) layer, manufactured as a Cu/GO/SiO 2 /Pt structure, which could be resistively switched in a vaporless environment. The X-ray photoelectron spectra depth profile of this structure showed that the GO film caused Cu ionization in a vaporless environment with migration of Cu ions in an electrical field to the Pt electrode.…”
mentioning
confidence: 99%